Pengaruh Shopping Lifestyle dan Brand Image Terhadap Purchase Decision Dalam Menggunakan Metode COD di Platform Shopee Pada Mahasiswa Fakultas Ekonomi Universitas Garut - Hilman Rismanto; Intan Permatasari; Anto Purwanto; Sintia Rahmawati; Pani Agustriani (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study examines consumer behavior in purchase decision-making on the Shopee e-commerce platform, particularly among consumers who use the Cash on Delivery (COD) payment method. The object of this research is Shopee users who choose the COD system when making online purchase transactions, as this payment method is perceived to provide greater security, convenience, and flexibility in online shopping. The research problem arises from inconsistencies in previous empirical findings regarding the influence of lifestyle and brand image on purchase decisions, as well as the limited number of studies that specifically investigate the behavior of Shopee consumers using the COD payment method. Therefore, this study aims to analyze the effect of lifestyle and brand image on the purchase decisions of Shopee consumers who use COD, both partially and simultaneously. This research employs a quantitative approach using a survey method. Data were collected through the distribution of questionnaires to respondents selected using a purposive sampling technique. The research instruments were tested for validity and reliability to ensure measurement accuracy. Data analysis was conducted using multiple linear regression with a significance level of 0.05, supported by classical assumption tests, t-tests, F-tests, and the coefficient of determination. The results indicate that lifestyle has a positive and significant effect on the purchase decisions of Shopee consumers using COD, suggesting that consumers’ activities, interests, and opinions play an important role in shaping purchase decisions. In contrast, brand image does not have a significant partial effect on purchase decisions. Simultaneously, lifestyle and brand image contribute to explaining variations in purchase decisions, although other factors outside the research model also influence consumer behavior. In conclusion, the purchase decisions of Shopee consumers using the COD payment method are more strongly influenced by internal factors, particularly lifestyle, than by brand image.